Reliability and Utility of the Skills.Lab Arena as A Real-Time Measurement Technology for Soccer Technique and Cognitive Performance. - Dolata, Michał; Zwierko, Teresa; Bojkowski, Łukasz; Moran, Brandon; Śliwowski, Robert (Journal of Sports Science & Medicine, 2025)
While motor and technical skills are typically assessed through field-based soccer tests, cognitive skills are usually evaluated in controlled laboratory environments. The Skills.Lab Arena is a newly developed testing and training device that enables motor, technical, and cognitive assessments in a soccer-specific setting. This study evaluated the reliability and usefulness of the Skills.Lab Arena technology. In a test--retest design (7 days, 1 month), 31 young soccer players (age, 13.5 ± 0.5 years) performed 10 trials of technical and motor-cognitive tests. Absolute and relative intersession reliability were determined using the intraclass correlation coefficient (ICC) and coefficient of variation (CV). Bland-Altman analysis was used to assess agreement, mean differences, and limits of agreement (LoA). A repeated-measures ANOVA was applied to identify potential learning effects between test sessions. The smallest worthwhile change and typical error (TE) were calculated to assess the intersession usefulness of the tests. The Skills.Lab Arena tests demonstrated good relative and absolute intersession reliability, with ICC values ranging from 0.75 to 0.89 for time-based tasks and 0.71 to 0.91 for accuracy- based tasks. Bland-Altman analysis revealed minimal mean differences with acceptable 95% LoA. CV values ranged from 1.78% to 4.5% for time-based tasks and were slightly higher, ranging from 8.08% to 19.87%, for accuracy-based tasks. Learning effects were observed in one ball-related agility test. In light of the results, the Skills.Lab Arena can be considered a reliable diagnostic tool for assessing motor-cognitive performance in young soccer players. However, despite its reliability, further validation is needed before it can be recommended for practical use.